IMPROVEMENT OF SYSTEMS OF TECHNICAL WATER SUPPLY WITH COOLING TOWERS FOR HEAT POWER PLANTS TECHNICAL AND ECONOMIC INDICATORS PERFECTION. Part 2 - Yu. A. Zenovich-Leshkevich-Olpinskiy; N. V. Shiroglazova; A. Yu. Zenovich-Leshkevich-Olpinskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The method of calculation of economic efficiency that can be universal and is suitable for feasibility study of modernization of irrigation and water distribution system of cooling towers has been developed. The method takes into account the effect of lower pressure exhaust steam in the condenser by lowering the temperature of the cooling water outlet of a cooling tower that aims at improvement of technical and economic indicators of heat power plants. The practical results of the modernization of irrigation and water distribution system of a cooling tower are presented. As a result, the application of new irrigation and water distribution systems of cooling towers will make it possible to increase the cooling efficiency by more than 4 оС and, therefore, to obtain the fuel savings by improving the vacuum in the turbine condensers. In addition, the available capacity of CHP in the summer period is increased. The results of the work, the experience of modernization of irrigation and water distribution systems of the Gomel CHP-2 cooling towers system, as well as the and methods of calculating of its efficiency can be disseminated for upgrading similar facilities at the power plants of the Belarusian energy system. Some measures are prosed to improve recycling systems, cooling towers and their structures; such measures might significantly improve the reliability and efficiency of technical water supply systems of heat power plants.